The performance of sCD25 and CTLs degranulation test for screening patients with primary hemophagocytic lymphohistiocytosis: a large-scale multicenter study in China - Zheng, Wenshuai; Chen, Zhaoguang; Cai, Yibo; Wu, Zongze; Du, Zhenlan; Li, Xiaohong; Li, Beicheng; Zhu, Shibin; Ning, Hongmei (Frontiers in Immunology, 2025)
BackgroundHemophagocytic lymphohistiocytosis can be classified as primary HLH (pHLH) and secondary HLH. The early identify of pHLH can facilitate successful treatment. The rapid screening test greatly facilitated the diagnostic process of pHLH. However, there are rare studies to explore the ability of sCD25 and cytotoxic T lymphocytes (CTLs) degranulation test to rapidly screen pHLH.MethodsWe validated the accuracies of sCD25 and CTLs degranulation test in screening pHLH in 1224 clinically confirmed or suspected HLH patients through calculating area under the curve (AUC) and diagnostic parameters at optimal threshold.ResultsThe sensitivities of sCD25 to identify pHLH with defects in cytotoxic pathway genes was 75.9%, with specificities of 57.3% and AUC of 0.640. The sensitivities of CTLs degranulation test to identify pHLH with defects in degranulation pathway genes was 87.0%, with specificities of 69.0% and AUC of 0.794. The sensitivities of combination of sCD25 and CTLs degranulation test to identify pHLH with defects in cytotoxic pathway genes was 90.0%, with specificities of 69.8% and AUC of 0.833.ConclusionFor identifying pHLH, CTLs degranulation test is more sensitive and no less specific than sCD25 and the combination of sCD25 and CTLs degranulation test can improve the accuracy further.